2011
DOI: 10.1348/026151010x494089
|View full text |Cite
|
Sign up to set email alerts
|

On-line ostracism affects children differently from adolescents and adults

Abstract: words (excluding references)How cyberostracism affects children and adults 2 Abstract This research examines adults', and for the first time, children's and adolescents' reaction to being ostracised and included, using an on-line game, 'Cyberball' with same and opposite sex players. Ostracism strongly threatened four primary needs (esteem, belonging, meaning and control) and lowered mood among 8-9-year olds, 13-14-year-olds, and adults. However, it did so in different ways. Ostracism threatened self-esteem nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
105
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 42 publications
11
105
1
Order By: Relevance
“…The effects of ostracism on children have rarely been examined in experimental research, and the current study used one of the few paradigms that has been shown to induce ostracism reliably and safely in both adults and children (e.g., Abrams et al, 2011;Williams et al, 2000). Consistent with the one previous study that has used the Cyberball paradigm to examine the effects of ostracism on primary needs in children (Abrams et al, 2011), we found that ostracized children reported a greater threat to primary needs than their included peers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of ostracism on children have rarely been examined in experimental research, and the current study used one of the few paradigms that has been shown to induce ostracism reliably and safely in both adults and children (e.g., Abrams et al, 2011;Williams et al, 2000). Consistent with the one previous study that has used the Cyberball paradigm to examine the effects of ostracism on primary needs in children (Abrams et al, 2011), we found that ostracized children reported a greater threat to primary needs than their included peers.…”
Section: Discussionmentioning
confidence: 99%
“…Like Abrams et al (2011), we modified the adult version of the paradigm for use with children by identifying the previously anonymous ''players'' with names and headshots of real children. The pairs of bogus players were OSTRACISM AND COGNITIVE PERFORMANCE 603 sex-matched to the participant (Ricky and Trevor for boys, and Sally and Cassie for girls).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations